2020
DOI: 10.1364/oe.390381
|View full text |Cite
|
Sign up to set email alerts
|

Background-suppressed SRS fingerprint imaging with a fully integrated system using a single optical parametric oscillator

Abstract: Stimulated Raman Scattering (SRS) imaging can be hampered by non-resonant parasitic signals that lead to imaging artifacts and eventually overwhelm the Raman signal of interest. Stimulated Raman gain opposite loss detection (SRGOLD) is a three-beam excitation scheme capable of suppressing this nonlinear background while enhancing the resonant Raman signal. We present here a compact electro-optical system for SRGOLD excitation which conveniently exploits the idler beam generated by an optical parametric oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…For CARSM, they are negligible by using excitation light with long wavelength, proper power and repetition rate [118][119][120]. In SRSM, nonlinear absorption is avoided for reducing the risk of photodamage and photobleaching because of background-free and long wavelength for excitation [118,121]. Furthermore, as involving only virtual state without energy deposition, SHGM brings little photodamage or photobleaching by increasing the repetition rate that keeps the peak intensity below damage threshold [122,123].…”
Section: Discussionmentioning
confidence: 99%
“…For CARSM, they are negligible by using excitation light with long wavelength, proper power and repetition rate [118][119][120]. In SRSM, nonlinear absorption is avoided for reducing the risk of photodamage and photobleaching because of background-free and long wavelength for excitation [118,121]. Furthermore, as involving only virtual state without energy deposition, SHGM brings little photodamage or photobleaching by increasing the repetition rate that keeps the peak intensity below damage threshold [122,123].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The optical parametric oscillator (OPO) based on the quasi-phase matching (QPM) technology can realize the tuning and expansion of the laser wavelength, which provides more possibilities for laser applications in many fields of science and technology including laser measurement, 7,8 and fingerprint imaging. 9 Periodically poled LiNbO 3 (PPLN), MgO-doped PPLN (PPMgLN), and periodically poled LiTaO 3 (PPLT) crystals are commonly used. By changing the grating period and temperature of these periodically poled crystals, a tunable laser output covering visible to mid-infrared can be obtained to meet different needs.…”
Section: Introductionmentioning
confidence: 99%
“…Near‐infrared lasers have important applications in nonlinear optics, material processing, medical diagnosis, laser ranging, and other fields 1‐6 . The optical parametric oscillator (OPO) based on the quasi‐phase matching (QPM) technology can realize the tuning and expansion of the laser wavelength, which provides more possibilities for laser applications in many fields of science and technology including laser measurement, 7,8 and fingerprint imaging 9 . Periodically poled LiNbO 3 (PPLN), MgO‐doped PPLN (PPMgLN), and periodically poled LiTaO 3 (PPLT) crystals are commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7‐11 ] However, recent studies have shown that thermal lensing or thermal scattering, two‐photon (two‐color) absorption (TPA), and cross‐phase modulation (XPM) lead to parasitic signatures on the SRS signal. [ 12‐15 ] Especially, artifacts due to XPM distort the line shape of the stimulated Raman signal and become more relevant for high pulse energies and ultra‐short pulse durations as used in a number of experiments. [ 16‐20 ]…”
Section: Introductionmentioning
confidence: 99%